2019
DOI: 10.5897/ajps2019.1851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rooting media and indole-3-butyric acid (IBA) concentration on rooting and shoot development of Duranta erecta tip cuttings

Abstract: Duranta erecta is popularly grown as an ornamental plant in tropical and semi-tropical gardens. Current demands for the shrub have prompted the need for effective propagation methods. In this study, the influence of indole-3butyric acid (IBA) hormone concentration and media on rooting of D. erecta propagated from tip cuttings under greenhouse conditions were investigated. IBA hormone was used in three concentrations (2500, 5000, and 7500 ppm) and 0 ppm was the control. The study consisted of three media types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…IBA has a significant influence on rooting capacity and is an important auxin for the regulation of adventitious root formation; furthermore, it is a stimulant hormone, as evidenced by the fact that IBA-treated cuttings have higher rooting percentages, more roots, and longer root lengths than untreated cuttings [14,16]. Consistent with other research [15,17], we found that pretreatment with IBA improved rooting in stem cuttings. This is due to the fact that the chemical accelerates rooting and stimulates adventitious root growth [18,20].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…IBA has a significant influence on rooting capacity and is an important auxin for the regulation of adventitious root formation; furthermore, it is a stimulant hormone, as evidenced by the fact that IBA-treated cuttings have higher rooting percentages, more roots, and longer root lengths than untreated cuttings [14,16]. Consistent with other research [15,17], we found that pretreatment with IBA improved rooting in stem cuttings. This is due to the fact that the chemical accelerates rooting and stimulates adventitious root growth [18,20].…”
Section: Introductionsupporting
confidence: 90%
“…Auxins have the biggest impact on rooting [14]. The most common auxin used for rooting olive cuttings is indole butyric acid [15,16]. Using indole butyric acid (IBA), a growth regulator, as a pretreatment for plant cuttings to facilitate their propagation has been commonplace [12].…”
Section: Introductionmentioning
confidence: 99%
“…IBA at 4000 ppm induced maximum rooting and produce high quality planting stock in Swietenia macrophylla (Azad and Matin, 2015). While for Duranta erecta 5000 ppm was the best for rooting and furthers than that the inhibitory effects on the rooting was apparent (Shiri et al, 2019). IBA treated cuttings produced higher rooting percentage, number of roots and root length than untreated cuttings revealing a strong IBA influence on rooting ability of stem cuttings in Swietenia macrophylla (Azad and Matin, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…IBA plays significant role in enhancing rooting process (root hair elongation, later root development and formation of adventitious roots) by involving in physiological process of cell division, cell enlargement and interaction with other hormones through different mechanisms (Zimmerman and Wilcoxon, 1935;Gehlot et al, 2014). Madhavan et al (2021), Sabatino et al (2014), Rahbin et al (2012) and Shiri et al (2019) reported enhancement of root length with the use of IBA in grapes, night jessamine (Cestrum nocturnum), silver germander (Teucrium fruticans) and Duranta errecta respectively. In Dragon fruit, Seran and Thiresh (2015) observed longest root length in cutting treated with 8000 ppm and 6000 ppm IBA.…”
Section: Resultsmentioning
confidence: 99%